Design and development for detection and prevention of ATM skimming frauds - Sultan Saleem Khalaf Al Hattali; Shaik Mazhar Hussain; Anilloy Frank (Institute of Advanced Engineering and Science, 2020)
ATM Skimming is a major concern that needs to be addressed with a specific solution. ATM Skimming is done in two steps. One is stealing the Personal Information that is stored on the Debit card / Credit card using Rain cover connected to the card reader slot (ATM’s real card slot). The second is installing a Fake keypad that can capture the pin code when the card holder enters pin details. Few researchers have proposed solutions to address the issue using Image Processing techniques. However, it does not provide a complete solution in a long term. Hence it is of paramount importance to provide ATM with high security features. In order to solve the issue of ATM Skimming, An Embedded System design is proposed. The research is carried out in two phases. One is detection phase and the second is Prevention Phase. In the detection phase, Hardware components such as Arduino Mega, Force Sensing Resistor (FSR), GPS, GSM and Buzzer are used. Arduino Mega acts as a Central Processor that processes the information received from Force sensing resistor (FSR) and send SMS Messages to ROP and Bank Officials using GSM and informing them about the ATM Location using GPS where the Fraud is taking place. Buzzer can be used at the ATM Locations to alert nearby people. In the prevention Phase, as a preventive measure a Onetime password (OTP) technique is used. If a fraudster somehow succeeds in Fixing fake key pad and Rain Cover at ATM’s real card slot, When he tries to insert debit card, An OTP will be generated and is sent to the Card Holder which in turn he can know someone is trying to make Transactions and quickly he can ask bank officials to Block his account and inform ROP about the same. Expected findings of the proposed work is to detect Fake keypads and Fake card readers using FSR placed at the edges of Original Keypad and card reader slot. Sending messages to ROP, BANK OFFICIALS and CARD HOLDER using GSM. ATM locations are identified using GPS. Buzzers are used to alert nearby people.